Management of Guillain-Barré Syndrome - Gopalakrishna, Kadarapura N.; Ramesh, Venkatapura J. (Journal of Neuroanaesthesiology and Critical Care, 2019)
Guillain-Barré syndrome (GBS) is the most common, immune-mediated acute polyneuropathy characterized by variable degree of motor weakness, often presenting with quadriparesis. GBS with respiratory failure requiring endotracheal intubation with mechanical ventilation is common, affecting approximately 30% of patients. In addition, they present with sensory features, cranial nerve involvement, and autonomic disturbance. The majority of GBS patients have preceding respiratory tract infection or gastroenteritis. The diagnosis of GBS is based on clinical features supported by cerebrospinal fluid (CSF) examination and nerve conduction studies. Early course of the GBS requires meticulous monitoring and early initiation of immunotherapy. Plasma exchange (PE) and intravenous immunoglobulin (IVIg) are the proven therapies, and both have been shown to be equally effective. General supportive care is an important part of management of GBS. A multidisciplinary approach to prevent and manage potential complications in rapidly progressing GBS is important to reduce morbidity and mortality.
Keywords: Guillain-Barré syndrome; immunotherapy; plasma exchange; immunoglobulin